ELEMENTAL ANALYSIS AND BIOLOGICAL STUDIES OF PHYSALIS ANGULATA L. USING WAVE LENGTH-DISPERSIVE X-RAY FLUORESCENCE TECHNIQUE, WAVELENGTH DISPERSION X-RAY FLUORESCENCE, FROM RAJASTHAN - Preet, Raman; Gupta, Raghbir Chand; Pradhan, Saroj Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Physalis angulata L. is an important medicinal plant, commonly known by different names such as mullaca, wintercherry, camapu, cutleaf, and referred as pilu,â€ by local tribal people of Rajasthan. This plant species is distributed from temperate to tropical region of the world. Traditionally, it has anticancerous, antimycobacterial, and anticoagulant properties. The juice is used in the treatment of earache, jaundice, fever, gonorrhea bladder diseases, etc., cytological exploration of the species from Rajasthan revels the existence of two cytotypes diploid (2n=12) and tetraploid (2n=24). This study is undertaken to identify the total mineral content of both the cytotypes from different plant parts, i.e., fruit, leaf, stem, and roots by wavelengthÂ dispersion X-ray fluorescence technique which is a simple method, recognized as a nondestructive technique to determine the elements from the rawÂ plant material without any chemical treatment and helps to ascertain the nutritional role. The analysis of mineral content led to the identificationÂ and concentration analysis of twenty-seven elements in diploid cytotype and twenty-five in tetraploid cytotype. The percentage value of potassiumÂ (5.52%); iron (0.50%) and selenium (0.0042%) is reported to be higher in diploid cytotype and the amount of calcium (2.15%); magnesium (0.75%)Â and zinc (0.0075%) are higher in tetraploid cytotype. The amount of most of the minerals is higher in tetraploid cytotype as compared to the diploidÂ cytotype. This information is very helpful in standardization of herbal products as this plant species is widely used for its medicinal benefits.